Geologi dan Karakteristik Batubara Daerah Kampung Klasari, Distrik Moisegen, Kab. Sorong, Provinsi Papua Barat Daya - Dana Christina Naomi Mambrasar; Fitryane Lihawa; Noviar Akase (Journal of Applied Geoscience and Engineering, 2026)
The purpose of the study is to examine the coal quality features and geological conditions in Klasari Village, Moisegen District, Sorong Regency, South-west Papua Province. Coal in the study area occurs as intercalations within claystone units and exhibits physical characteristics indicating a low degree of coalification. Laboratory testing was conducted using proximate analysis to determine coal quality parameters, including moisture content, ash content, volatile matter, and fixed carbon. The results show moisture values ranging from 6.21 to 13.95%, ash content from 2.1 to 14.4%, volatile matter from 33.7 to 38.3%, fixed carbon from 6 to 6.9%, and calorific values between 3,379 and 3,710 kcal/kg. Based on the ASTM D388 classification, the coal from the study area is classified as lignite. These findings indicate that the coal was formed in a swamp–fluvial depositional environment under reductive conditions that were not favorable for further coalification processes. Therefore, the coal is considered low-rank and is more suitable for small-scale energy utilization or low-power industrial applications.